Literacy of the Cihideung Village Community towards Sasapian Arts - Magfiroh, Valencia Sahara; Husna, Fathma Nailal; Maulida, Nasywa Gassani; Sadiyah, Neng Siti Nur; Hyangsewu, Pandu (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This research discusses the literacy of the people of Cihideung Village towards sasapian art, a cultural heritage that has existed since 1910. Through the interview method, this study found that Sasapian art is not mere entertainment, but a tool in conveying philosophical values, such as togetherness, struggle, and respect for tradition. Despite challenges such as differences in religious views and the potential for misuse of the event, the community continues to preserve this art from time to time, even now aided by modern technology. The results of this study show that sasapian is a symbol of cultural identity that strengthens the social relations and spiritual values of the Cihideung Village community.